2000
DOI: 10.1161/01.cir.102.11.1283
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Atrial Flutter Isthmus in Postoperative Intra-Atrial Reentrant Tachycardia

Abstract: In most of our postoperative patients, the atrial flutter isthmus was part of the reentrant circuit. The fact that the atrial flutter isthmus is vulnerable to ablation suggests that whenever IART occurs late after repair of a congenital heart defect, the atrial flutter isthmus should be evaluated. These data support the theory that some form of conduction block between the vena cava is essential for the establishment of a stable substrate for the atrial flutter reentrant circuit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(91 citation statements)
references
References 23 publications
3
88
0
Order By: Relevance
“…Subsequent electrophysiology studies have demonstrated the key role played by the right atrial isthmus in typical right AFL (isthmus dependent right atrial macroreentry) (1,(57)(58)(59)(60). The right atrial isthmus is considered the area between the tricuspid valve annulus and the coronary sinus and the IVC.…”
Section: Aflmentioning
confidence: 99%
“…Subsequent electrophysiology studies have demonstrated the key role played by the right atrial isthmus in typical right AFL (isthmus dependent right atrial macroreentry) (1,(57)(58)(59)(60). The right atrial isthmus is considered the area between the tricuspid valve annulus and the coronary sinus and the IVC.…”
Section: Aflmentioning
confidence: 99%
“…Cavotricuspid isthmus-dependent flutter is common in patients with prior atrial surgery, and both CTI-and non-CTI-dependent macro-reentry circuits often coexist in a single patient. 173,[176][177][178][179][180] Successful ablation is dependent on identifying a critical portion of the re-entry circuit where it can be interrupted with either one or a line of RF applications.…”
Section: A Catheter Ablation and Mapping Of Non-cavotricuspid Isthmumentioning
confidence: 99%
“…113,172,173,[176][177][178][179][180][181][182][183] The incision is often placed in the lateral right atrium; the re-entry wavefront circulates around the incision. A line of ablation lesions extending from the inferior margin of the scar to the inferior vena cava, or from the superior margin of the scar to the SVC, can interrupt the circuit, but it can also be difficult to complete.…”
Section: A Catheter Ablation and Mapping Of Non-cavotricuspid Isthmumentioning
confidence: 99%
“…11,12 It was shown that right atrium surgery during septal defects closure or correction of other congenital heart anomalies represent another major cause of atrial re-entry arrhythmias. [13][14][15][16][17][18][19][20] Such tachycardias tend to have various localization due to individual anatomical features and surgical technique as well as the severity of atrial fibrosis. Incisional tachycardia can occur both during early and late postoperative period.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on young patients after surgical correction of congenital heart anomalies demonstrated average efficacy of radiofrequency ablation from 12 to 50% during more than 2 years of follow-up. 2,[14][15][16] The lack of randomized clinical trials is the main limitation when the effectiveness of incisional tachycardia treatment is estimated. The termination of arrhythmia during ablation doesn't always represent adequate clinical point of radical treatment.…”
Section: Introductionmentioning
confidence: 99%